Influence of Sensor Coating and Topography on Protein and Nanoparticle Interaction with Supported Lipid Bilayers - Yin, Hui (Langmuir : the ACS journal of surfaces and colloids, 2021)
Supported lipid bilayers (SLBs) have proven to be valuable model systems for studying the interactions of proteins, peptides, and nanoparticles with biological membranes. The physicochemical properties (e.g., topography, coating) of the solid substrate may affect the formation and properties of supported phospholipid bilayers, and thus, subsequent interactions with biomolecules or nanoparticles. Here, we examine the influence of support coating (SiO2 vs Si3N4) and topography [sensors with embedded vs protruding gold nanodisks for nanoplasmonic sensing (NPS)] on the formation and subsequent interactions of supported phospholipid bilayers with the model protein cytochrome c and with cationic polymer-wrapped quantum dots using quartz crystal microbalance with dissipation monitoring and NPS techniques. The specific protein and nanoparticle were chosen because they differ in the degree to which they penetrate the bilayer. We find that bilayer formation and subsequent non-penetrative association with cytochrome c were not significantly influenced by substrate composition or topography. In contrast, the interactions of nanoparticles with SLBs depended on the substrate composition. The substrate-dependence of nanoparticle adsorption is attributed to the more negative zeta-potential of the bilayers supported by the silica vs the silicon nitride substrate and to the penetration of the cationic polymer wrapping the nanoparticles into the bilayer. Our results indicate that the degree to which nanoscale analytes interact with SLBs may be influenced by the underlying substrate material